2003
DOI: 10.1177/0269881103017001688
|View full text |Cite
|
Sign up to set email alerts
|

The modulatory effects of dopamine D1 and D2 receptor function on object working memory in humans

Abstract: The role of dopamine D1 and D2 receptors in modulating object working memory in humans is poorly understood. The current study was designed to investigate the effects of D1 and D2 receptor modulation on object working memory. Twelve healthy subjects underwent testing under three conditions (0.05 mg pergolide (D1/D2 receptor agonist), 2.5 mg bromocriptine (D2 receptor agonist) and placebo] in a double-blind, placebo-controlled repeated measures design. Subjects performed the object working memory N-back task pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 50 publications
1
27
0
1
Order By: Relevance
“…The dose of 0.1 mg per day was selected based on prior studies showing positive effects of a single dose of pergolide on cognition (Kimberg and D'Esposito, 2003;Muller et al, 1998). A third study using a lower dose (0.05 mg) had no effect on cognitive performance (Bartholomeusz et al, 2003). The PLACEBO group (n ¼ 20, five females) received a standard placebo substance (99.5% mannitol, 0.5% erosil) in identical capsules.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dose of 0.1 mg per day was selected based on prior studies showing positive effects of a single dose of pergolide on cognition (Kimberg and D'Esposito, 2003;Muller et al, 1998). A third study using a lower dose (0.05 mg) had no effect on cognitive performance (Bartholomeusz et al, 2003). The PLACEBO group (n ¼ 20, five females) received a standard placebo substance (99.5% mannitol, 0.5% erosil) in identical capsules.…”
Section: Subjectsmentioning
confidence: 99%
“…Results for the mixed D1/D2-like receptor dopamine agonist pergolide are inconsistent as well: pergolide improved working memory in one study (Muller et al, 1998), was effective only in a subgroup of the studied sample (Kimberg and D'Esposito, 2003), or proved ineffective (Bartholomeusz et al, 2003;Roesch-Ely et al, 2005). Even under conditions of endogenous dopamine depletion via tyrosine/phenylalanine depletion, a deterioration of working memory performance was observed after pergolide administration (Ellis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are consequently affected in diseases with disturbed DA function such as Parkinson's syndrome or schizophrenia (Grace et al 1998). DAergic modulation on cognitive functions has long been investigated intensively, and the results at first glance revealed that DA-enhancing agents facilitated working and long-term memory, whereas DA receptor blockers impaired it (Luciana et al 1992;Kimberg et al 1997;Luciana and Collins 1997;Muller et al 1998;Mehta et al 1999Mehta et al , 2001Bartholomeusz et al 2003;Knecht et al 2004;Floel et al 2005). However, the DAergic influence on cognition might be not quite as simple as originally thought: It might depend on dosage, DAergic subreceptor specificity, and task characteristics (Kulisevsky 2000;Floresco and Phillips 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Such a focusing mechanism is particularly necessary for consolidation of cognitive functions related to learning and memory, which require long-term stabilization of one or a set of limited representations and suppression of other nonsignificant inputs in neural networks. Several studies have suggested the importance of DAergic focusing on cognition in humans (Kimberg et al 1997;Muller et al 1998;Mehta et al 1999;Bartholomeusz et al 2003;Knecht et al 2004;Floel et al 2005), but direct neurophysiological evidence for such a focusing action of DA in humans is still missing.…”
Section: Introductionmentioning
confidence: 99%